The topology of connections between rat prefrontal and temporal cortices - Bedwell, Stacey A.; Billett, E. Ellen; Crofts, Jonathan J.; MacDonald, Danielle M.; Tinsley, Chris J. (Frontiers in Systems Neuroscience, 2015)
Understanding the structural organisation of the prefrontal cortex (PFC) is an important step towards determining its functional organisation. Here we investigated the organisation of PFC using different neuronal tracers. We injected retrograde (Fluoro-Gold, 100nl) and anterograde (Biotinylated dextran amine (BDA) or Fluoro-Ruby, 100nl) tracers into sites within PFC subdivisions (prelimbic, ventral orbital, ventrolateral orbital, dorsolateral orbital) along a coronal axis within PFC. At each injection site one injection was made of the anterograde tracer and one injection was made of the retrograde tracer. The projection locations of retrogradely labelled neurons and anterogradely labelled axon terminals were then analysed in the temporal cortex: area Te, entorhinal and perirhinal cortex. We found evidence for an ordering of both the anterograde (anterior-posterior, dorsal-ventral and medial-lateral axes: p<0.001) and retrograde (anterior-posterior, dorsal-ventral and medial-lateral axes: p<0.001) connections of PFC. We observed that anterograde and retrograde labelling in ipsilateral temporal cortex (i.e. PFC inputs and outputs) often occurred reciprocally (i.e. the same brain region, such as area 35d in perirhinal cortex, contained anterograde and retrograde labelling). However, often the same specific columnar temporal cortex regions contained only either labelling of retrograde or anterograde tracer, indicating that PFC inputs and outputs are frequently non-matched.